2023
DOI: 10.3390/pharmaceutics15020308
|View full text |Cite
|
Sign up to set email alerts
|

Focal Photocoagulation as an Adjunctive Therapy to Reduce the Burden of Intravitreal Injections in Macula Edema Patients, the LyoMAC2 Study

Abstract: Aim:To assess the efficacy of focal photocoagulation of capillary macroaneurysms (CMA) to reduce the burden of intravitreal injections (IVI) in patients with macular edema (ME). Materials and Methods: Retrospective multicenter study in patients with diabetic ME or ME secondary to retinal vein occlusion (ME-RVO). CMA associated with ME were selectively photocoagulated. Patients were followed for one year after photocoagulation. Results: 93 eyes of 76 patients were included in this study. At 6 months after the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Another study of chronic macular oedema (secondary to diabetes and vein occlusion) has found that 66.3% of patients had macular TELCAPS [ 28 ]. Furthermore, treating these TELCAPS allowed for the reduction of the interval between intravitreal injections [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study of chronic macular oedema (secondary to diabetes and vein occlusion) has found that 66.3% of patients had macular TELCAPS [ 28 ]. Furthermore, treating these TELCAPS allowed for the reduction of the interval between intravitreal injections [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Net Protocol I study showed no significant difference in 5-year visual prognosis between the 6-month delayed combined laser group and the early combined laser group, but delayed laser treatment reduced macular damage, eliminated the need for grid-pattern photocoagulation in about 56% of patients, and provided a better visual prognosis in patients with poor baseline VA (<20/50) with delayed laser treatment [15]. The LyoMAC2 study noted that focal photocoagulation of capillary macroaneurysm (CMA) was effective in reducing the number of injections in patients with chronic DME, at 12 months after laser treatment, the number of anti-VEGF treatments was reduced by nearly 50%, and the number of DEX-I treatments was reduced by 25% [82]. Laser therapy still has an irreplaceable role in the treatment of DME, and further studies are needed to explore the optimal timing of laser photocoagulation to provide better anatomical and functional improvement and to reduce the number of injections.…”
Section: Laser Therapymentioning
confidence: 99%
“…Paques et al identified the relatively large ICGA-positive area as telangiectatic capillaries (defined by a diameter larger than 150 µm on late-phase ICGA) [ 75 , 77 ]. Telangiectatic capillaries may be associated with chronic refractory macular edema [ 78 , 79 , 80 ], and focal direct laser photocoagulation of telangiectatic capillaries seems to be effective and safe for reducing the burden of anti-VEGF drugs in patients with refractory ME [ 81 ].…”
Section: Multimodal Imaging-guided Laser Therapymentioning
confidence: 99%
“…The types and settings of current laser are summarized in Figure 6 . Focal/grid laser photocoagulation is crucial in treating non-center-involved, clinically significant DME [ 6 , 22 , 81 ]. For center-involved DME, anti-VEGF therapy has become the gold standard treatment.…”
Section: The Current Role Of Laser Photocoagulation In the Era Of Int...mentioning
confidence: 99%